A Medal for Benny Movie Still - Paramount Pictures:::Creator::::::::::::
Joe Morales (Arturo de Cordova) after just having had a pot of beans dumped over him by his dance partner in Paramount Pictures 1945 production of 'A Medal for Benny.' This is the scene in which Lolita Sierra (Dorothy Lamour) begins to sympathize with him. According to caption, the production company was giving Lamour and de Cordova an opportunity to show their talents with this movie.